2018
DOI: 10.1055/a-0719-4903
|View full text |Cite
|
Sign up to set email alerts
|

B-Mode Transorbital Ultrasonography for the Diagnosis of Idiopathic Intracranial Hypertension: A Systematic Review and Meta-Analysis

Abstract: In patients with idiopathic intracranial hypertension (IIH), transorbital sonography (TOS) may reveal an enlargement of the optic nerve sheath diameter (ONSD) and the presence of optic disc elevation (ODE), as a sign of an increase in intracranial pressure (ICP). We systematically reviewed the TOS findings in adults with IIH. MEDLINE, EMBASE, Cochrane Library and CENTRAL (1966 – May 2017) were searched to identify studies reporting data on patients with IIH assessed by B mode-TOS. Data were extracted and inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…With further technical and methodological development in the last decades, enabling the quantification of diameters of optic nerve and his sheaths, TOS became a promising novel diagnostic tool in neurology and intensive care medicine. The main areas of application are diseases with increased intracranial pressure such as idiopathic intracranial hypertension, intracranial hemorrhage, and neuro‐traumatological diseases . In this context, TOS provides a helpful diagnostic tool for early prognostication of hypoxic‐ischemic encephalopathy after cardiac arrest .…”
Section: Introductionmentioning
confidence: 99%
“…With further technical and methodological development in the last decades, enabling the quantification of diameters of optic nerve and his sheaths, TOS became a promising novel diagnostic tool in neurology and intensive care medicine. The main areas of application are diseases with increased intracranial pressure such as idiopathic intracranial hypertension, intracranial hemorrhage, and neuro‐traumatological diseases . In this context, TOS provides a helpful diagnostic tool for early prognostication of hypoxic‐ischemic encephalopathy after cardiac arrest .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they demonstrated that the ONSD reflects an immediate change in ICP and changes almost concurrently with rapid ICP variations [2,4]. However, the optimal ONSD cutoff point for detection of increased ICP has not been well established, the range of proposed values varies from 4.8 to 5.9 mm [5][6][7][8][9]. Available data regarding normal ONSD are also inconclusive, with a wide inter-individual range of ONSD in the general healthy population [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In idiopathic normal-pressure hydrocephalus, sonography of ONSD was shown to be a reliable diagnostic supplement to spinal tap tests [27]. Furthermore, ONSD has consistently been found to be bigger in patients with idiopathic intracranial hypertension than in controls [28], whereas transorbital ultrasound of OND did not reveal such a difference [29]. In SIH, it has been shown that dynamic ultrasound of the ONSD can be used as a non-invasive tool for diagnosis [13] and follow-up after surgical treatment of the CSF leak [23].…”
Section: Discussionmentioning
confidence: 99%